Testicular Pathology: A Four Years Study at BP Koirala Memorial Cancer Hospital - Bastakoti, Shankar; Lamichhane, Nirmal; Bhatta, Ranjan R.; Pandey, Greta; Jha, Nandita; Singh, Ranjita; Dhungana, Ishan; Uprety, Suraj; Bastakoti, Sudip (Annapurna Journal of Health Sciences, 2023)
Introduction: Cancer of testes are relatively rare cancer accounting around 1 % cancer in male. The commonest presentation of testicular tumor is a nodule or painless swelling of one or both testicle.Methods: Retrospective study was performed in the Department of Pathology, BP Koirala Memorial Cancer Hospital from January 2016 to December 2019 (4 years). Tumour typing and subtyping was done according to WHO classification. The objective of the study was to assess clinico-pathological spectrum of testicular disease and to evaluate histopathological diagnosis and subtypes in Prime Oncology Centre of Nepal. All data were entered in MS excel and descriptive analysis was done.Results: A total of 69 cases of orchidectomy with age ranges from 2 years to 84 years were included. 83% of cases are neoplastic and most common was Germ cell tumor. In our study, testicular tumors showed a diverse histopathology features and Germ cell tumors were the dominating ones. Among the individual germ cell tumors, Seminoma were the most common followed by Mixed GCT. Testicular tumors were the most common in third and fourth decades of life.Conclusion: Most common neoplasm in testes was germ cell tumor and of which Seminoma was most frequent.Histopathological examination is necessary to execute an accurate diagnosis of testicular swellings and further treatment.